Zadłużenie jednostek samorządu terytorialnego w wojewódzkich funduszach ochrony środowiska i gospodarki wodnej na przykładzie województwa łódzkiego - Babczuk, Arkadiusz (Municipal Debt in Voivodeship Funds for Environmental Protection and Water Management - Case Study: the Region of Łódź, 2006)
The subject of this article is the presentation of municipal debt in the Voivodeship Fund for Environmental Protection and Water Management in Łódź. Loans from this fund are especially important in financial management of rural municipalities and municipalities encompasses villages and small towns. Loans from this fund are 35% of rural municipalities debt and 20% of municipalities encompasses villages and small towns debt. Investments of these municipalities are strongly dependent on the Fund for Environmental Protection and Water Management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 529-538